Phrixosoma concavifrons – a sexually dimorphic Phrixosomatini (Coleoptera: Curculionidae) from the Udzungwa mountains in Tanzania - Jordal, Bjarte H. (Zootaxa, 2012)
A new species of Phrixosoma from Tanzania is described and illustrated. This is a unique species for the genus in havinga strongly concave female frons. Several characters are described for the first time for this genus, including male andfemale genitalia, mouthparts, thoracic sutures, and several overlooked features of the mesoand metatibiae and sternal processes.